2016
DOI: 10.1016/j.cct.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

A study protocol testing the implementation, efficacy, and cost effectiveness of the ezParent program in pediatric primary care

Abstract: Integrating and evaluating the implementation of the ezParent in pediatric primary care is an innovative opportunity to promote positive parenting with potential for universal access to the preschool population and for low cost by building on existing infrastructure in pediatric primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…These types of interventions were usually adapted from existing EBIs (71%). eHealth strategies applied include web-based parenting modules (included 4 to 12 interactive or structured parenting sessions), with (44, 45, 5253, 54, 56, 57) or without (42, 47, 48, 50, 55) additional e-communication or e-support for parents (e.g., phone coaching, e-reminders, feedback messaging, email, social media groups). There were also some studies focused on parent support interventions (including information and emotion support) and wellness promotion (purpose) for families of children with challenging behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of interventions were usually adapted from existing EBIs (71%). eHealth strategies applied include web-based parenting modules (included 4 to 12 interactive or structured parenting sessions), with (44, 45, 5253, 54, 56, 57) or without (42, 47, 48, 50, 55) additional e-communication or e-support for parents (e.g., phone coaching, e-reminders, feedback messaging, email, social media groups). There were also some studies focused on parent support interventions (including information and emotion support) and wellness promotion (purpose) for families of children with challenging behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Average length of time per visit was 14.1 min (SD = 17.1). Participants completed on average 82% of the modules (out of 6 total modules) (47).…”
Section: Resultsmentioning
confidence: 99%
“…Messaging and resources could be delivered via text throughout the perinatal period with coordinated in-person prevention messaging during maternal doctor visits, ultrasounds, and well-child visits in the pediatric or family practice settings. Pediatric wellchild visits could provide a natural setting for disseminating prevention resources and implementing many aspects of prevention (e.g., Breitenstein et al 2016;Glassgow et al 2018). Currently, only 19 states require a child to have a physical medical exam before starting school; 41 states require a vision screening.…”
Section: Leverage Existing Infrastructurementioning
confidence: 99%
“…Providing this information in healthcare settings as health promotion could reduce the stigma of parents seeking support. Research has demonstrated the feasibility and effectiveness of providing parenting services and parent training in healthcare settings (e.g., Breitenstein et al 2016;Risser et al 2016;Tapia et al 2006).…”
Section: Leverage Existing Infrastructurementioning
confidence: 99%
See 1 more Smart Citation